Risk factors associated with acute respiratory illnesses in athletes: a systematic review by a subgroup of the IOC consensus on 'acute respiratory illness in the athlete'. Issue 11 (11th March 2022) - Derman, Wayne; Badenhorst, Marelise; Eken, Maaike; Gomez-Ezeiza, Josu; Fitzpatrick, Jane; Gleeson, Maree; Kunorozva, Lovemore; Mjosund, Katja; Mountjoy, Margo; Sewry, Nicola; Schwellnus, Martin
Abstract : Objective: To review risk factors associated with acute respiratory illness (ARill) in athletes, including non-infectious ARill and suspected or confirmed acute respiratory infections (ARinf). Design: Systematic review. Data sources: Electronic databases: PubMed-Medline, EbscoHost and Web of Science. Eligibility criteria: Original research articles published between January 1990 and July 2020 in English were searched for prospective and retrospective full text studies that reported quantitative data on risk factors associated with ARill/ARinf in athletes, at any level of performance (elite/non-elite), aged 15–65 years. Results: 48 studies (n=19 390 athletes) were included in the study. Risk factors associated with ARill/ARinf were: increased training monotony, endurance training programmes, lack of tapering, training during winter or at altitude, international travel and vitamin D deficits. Low tear-(SIgA) and salivary-(IgA) were immune biomarkers associated with ARill/ARinf. Conclusions: Modifiable training and environmental risk factors could be considered by sports coaches and athletes to reduce the risk of ARill/ARinf. Clinicians working with athletes can consider assessing and treating specific nutritional deficiencies such as vitamin D. More research regarding the role and clinical application of measuring immune biomarkers in athletes at high risk of ARill/ARinf is warranted. PROSPERO registration number: CRD42020160928.